2016
DOI: 10.1038/ismej.2016.98
|View full text |Cite
|
Sign up to set email alerts
|

Metal stressors consistently modulate bacterial conjugal plasmid uptake potential in a phylogenetically conserved manner

Abstract: The environmental stimulants and inhibitors of conjugal plasmid transfer in microbial communities are poorly understood. Specifically, it is not known whether exposure to stressors may cause a community to alter its plasmid uptake ability. We assessed whether metals (Cu, Cd, Ni, Zn) and one metalloid (As), at concentrations causing partial growth inhibition, modulate community permissiveness (that is, uptake ability) against a broad-host-range IncP-type plasmid (pKJK5). Cells were extracted from an agricultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
103
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 70 publications
7
103
4
Order By: Relevance
“…Also, although the general tendency was to decrease transfer, for some specific OTUs transfer did actually increase. Overall, these results indicate a profound effect of metal-caused stress on conjugative transfer, measured as permissiveness, which has been defined as "the ability of a community to receive a plasmid, both in terms of transfer frequency and phylogeny" (Klumper et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, although the general tendency was to decrease transfer, for some specific OTUs transfer did actually increase. Overall, these results indicate a profound effect of metal-caused stress on conjugative transfer, measured as permissiveness, which has been defined as "the ability of a community to receive a plasmid, both in terms of transfer frequency and phylogeny" (Klumper et al, 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…A more recent report of coexistence and possible dissemination of multidrug and metal resistant plasmids was published by Fang et al, (2016). In a very elegant manner, Klumper et al, (2017) have shown that the presence of low concentrations of metal stressors such as Zn, Cd, Cu, Ni and As decreased the transfer of a broad-host-range IncP-type plasmid (pKJK5) to potential recipients extracted from an agricultural soil, however, transconjugants were distributed among 12 different bacterial phyla, indicating that the distribution pattern was unaffected. Also, although the general tendency was to decrease transfer, for some specific OTUs transfer did actually increase.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Metal stress could for 303 example increase the rate at which antibiotic and metal resistance evolves through 304 increased mutation rate (Lemire, Harrison and Turner 2013), which could subsequently be 305 fixed in the population through antibiotic or metal selection. Increased spread of resistance 306 could also result from metals impacting plasmid transfer (Klümper et al 2017(Klümper et al , 2019a. 307…”
mentioning
confidence: 99%
“…Therefore, these studies on animals or humans support the increase in ROS in the presence of these non-antibiotic pharmaceuticals. In addition to these non-antibiotic pharmaceuticals, biocides (e.g., triclosan) and heavy metals were also demonstrated to increase ROS generation levels, impose stress-response on bacteria, thus enhancing the uptake potential of conjugal plasmids 6062 . Further studies are required to confirm if other non-antibiotic pharmaceuticals follow this pattern of enhancing intracellular ROS generation and potentially contributing to increased bacterial gene transfer.…”
Section: Discussionmentioning
confidence: 99%